Analysis on judo specific and unspecific test - Santos Rodríguez, Luis; Prieto Saborit, José Antonio; González Díez, Vicente (Revista de Artes Marciales Asiáticas, 2012)
In specialized literature it is not easy to find test which give us information about judokas developing their specific kinetic habits. Although judo is included in sociomotor sports (Parlebas, 2001), judokas physical fitness is normally evaluated through test which come from other type of sports, mainly from phychomotor sports. At the same time, batteries as the battery Eurofit (Conseil de L´Europe, 1989), are use to evaluate perceptive-motors aspects. In this article, we describe some of the tests found in specific western bibliography. Once finished this analysis, we mention the need of creating test which value the reality of competition confrontation more specifically, and which can be reliable, objective and reproductive (López and cols. 2004) being easy and useful to the trainer as well.